1985
DOI: 10.2466/pms.1985.60.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Remembering Postdelivery Pain

Abstract: Memory for pain after delivery was assessed by means of a verbal rating scale. 238 young women giving birth to healthy babies as a result of spontaneous delivery were asked to rate intensity of pain immediately following delivery. A day or two later, they were asked to remember how much pain they had experienced immediately after delivery. Analysis showed that the recall of pain was fairly accurate, irrespective of personality type, the level of education, and the number of childbirths. The findings provide so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 15 publications
2
13
1
1
Order By: Relevance
“…Contrary to occasional reports of reciprocity in the literature (e.g., Melzack, 1984; but see Rofe & Algom, 1985), none of these variables evidenced a significant correlation with the rate of perceived or remembered pain. Note, however, that previous reports pertain to correlations with absolute judgments of pain, whereas the present data are based on correlations with a rate-of-growth parameter.…”
Section: Memorycontrasting
confidence: 96%
See 2 more Smart Citations
“…Contrary to occasional reports of reciprocity in the literature (e.g., Melzack, 1984; but see Rofe & Algom, 1985), none of these variables evidenced a significant correlation with the rate of perceived or remembered pain. Note, however, that previous reports pertain to correlations with absolute judgments of pain, whereas the present data are based on correlations with a rate-of-growth parameter.…”
Section: Memorycontrasting
confidence: 96%
“…Virtually all extant studies have relied on either a single retrospective rating of the entire experience of labor or on a few one-time ratings from different phases of labor (Bonnel & Boureau, 1985;Cogan, Henneborn, & Klopfer, 1980;Melzack, Kinch, Dobkin, Lebrun, & Taenzer, 1984;Melzack, Taenzer, Feldman, & Kinch, 1981;Nettelbladt, Fagerstrom, & Uddenberg, 1976;Niven & Gijsbers, 1984;Norvell, Gaston-Johansson, & Fridh, 1987;Pesce, 1987;Rofe & Algom, 1985). Yet it is highly questionable whether a single estimate or a handful of sporadic judgments can capture the full spectrum of sensations involved in so rich, intricate, and multifarious an experience as labor.…”
Section: Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study performed in Sweden, it was shown that the amount of pain and discomfort remembered was less than the amount of pain reported in labour by both primiparous and multiparous women 20 . Another study in Israel did not find differences between labour pains recorded immediately after delivery and recalled 2 days after 21 . Postpartum pain has not been a focus of investigations, probably because it is less severe than the pain in first and second stages of labour.…”
Section: Discussionmentioning
confidence: 85%
“…Auch Jamison et al [10] und Rachman u. Eyrl [18] fanden bei chronischen Schmerzpatienten eine Tendenz, mehrere Wochen zurücklie-gende Schmerzen in ihrem Ausmaß zu überschätzen. Andere Autoren [17,19,20] konnten jedoch zeigen, daß einmalige Schmerzepisoden oder bislang nicht aufgetretene akute Schmerzereignisse (z.B. Geburtsschmerz) von nicht vorbelasteten Personen sehr genau erinnert werden können.…”
Section: Va-scoresunclassified